Visualising the urethra for prostate radiotherapy planning. Issue 3 (24th May 2021) - Richardson, Matthew; Skehan, Kate; Wilton, Lee; Sams, Joshua; Samuels, Justin; Goodwin, Jonathan; Greer, Peter; Sridharan, Swetha; Martin, Jarad
Abstract: Introduction: The prostatic urethra is an organ at risk for prostate radiotherapy with genitourinary toxicities a common side effect. Many external beam radiation therapy protocols call for urethral sparing, and with modulated radiotherapy techniques, the radiation dose distribution can be controlled so that maximum doses do not fall within the prostatic urethral volume. Whilst traditional diagnostic MRI sequences provide excellent delineation of the prostate, uncertainty often remains as to the true path of the urethra within the gland. This study aims to assess if a high‐resolution isotropic 3D T2 MRI series can reduce inter‐observer variability in urethral delineation for radiotherapy planning. Methods: Five independent observers contoured the prostatic urethra for ten patients on three data sets; a 2 mm axial CT, a diagnostic 3 mm axial T2 TSE MRI and a 0.9 mm isotropic 3D T2 SPACE MRI. The observers were blinded from each other's contours. A Dice Similarity Coefficient (DSC) score was calculated using the intersection and union of the five observer contours vs an expert reference contour for each data set. Results: The mean DSC of the observer vs reference contours was 0.47 for CT, 0.62 for T2 TSE and 0.78 for T2 SPACE ( P < 0.001). Conclusions: The introduction of a 0.9 mm isotropic 3D T2 SPACE MRI for treatment planning provides improved urethral visualisation and can lead to a significant reduction in inter‐observer variation in prostatic urethral contouring. Abstract : Whilst traditional diagnostic MRI sequences provide excellent delineation of the prostate, uncertainty often remains as to the true path of the urethra within the gland. This study aims to assess if a high resolution isotropic 3D T2 MRI series can reduce inter‐observer variability in urethral delineation for radiotherapy planning.